Edukasi Masyarakat Tentang Peran Makanan dalam Menjaga Sistem Imunitas di Desa Dua Paya Kabupaten Pidie - Tuti Sahara; Nurlela Mufida; Yuliana Yuliana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
A good immune system is the key to avoiding viral, bacterial, fungal, and parasitic infections. A person's immune status affects the risk of being infected by various viruses and bacteria, various studies have been conducted to increase the immune system. One of them is through proper and balanced nutritional intake and utilizing functional foods based on local food. The purpose of this activity is to increase public knowledge regarding the role of food in improving the immune system. Method This community service activity is carried out through the provision of education (counseling) with the lecture method. The target is the general public in Paya Dua village in Menasah (surau) with a capacity of 100 people. The material was delivered directly which was divided into lecture sessions and question and answer sessions or sharing. The results of education related to the role of food in improving the immune system provide benefits to the community, impacting the increase in public knowledge about food that can maintain the personal and environmental immunity system. Conclusion The community gained knowledge about foods that contain balanced nutrition and increased public knowledge regarding the role of balanced nutrition in food that affects the improvement of the immune system. It is hoped that through this education and socialization, the community will be able to maintain health by improving the immune system in the family and community.